Restructuring Electricity Markets when Demand is Uncertain: Effects on Capacity Investments, Prices and Welfare - Stefan Buehler; Anette Boom (Copenhagen Business School (CBS), Department of Economics, 2006)
We examine the effects of reorganizing electricity markets on ca- pacity investments, retail prices and welfare when demand is uncer- tain. We study the following market configurations: (i) integrated monopoly, (ii) integrated duopoly with wholesale trade, and (iii) sep- arated duopoly with wholesale trade. Assuming that wholesale prices can react to changes in retail prices (but not vice versa), we find that generators install sufficient capacity to serve retail demand in each market configuration, thus avoiding black-outs. Furthermore, aggre- gate capacity levels and retail prices are such that the separated (inte- grated) duopoly with wholesale trade performs best (worst) in terms of welfare.
hdl:10398/7589
Keywords: D42; D43; D44; L11; L12; L13; 330; Electricity; Investments; Generating Capacities; Vertical Integration; Monopoly and Competition